2010
DOI: 10.4037/ajcc2010902
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium After Colorectal Surgery in Older Patients

Abstract: Background Postoperative delirium in older patients results in worse outcomes and increased costs. The prevalence and predictors of postoperative delirium in patients undergoing major colorectal surgery are not clear. Objectives To determine the prevalence and predictors of postoperative delirium in older patients after major colorectal surgery. Methods Patients older than 50 years, without preexisting cognitive impairment, were recruited before surgery. These patients were assessed after surgery for delirium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 76 publications
0
25
2
7
Order By: Relevance
“…Postoperative delirium occurs at an incidence rate of 15-35% following gastrointestinal (GI) surgery in the elderly [1][2][3] . Symptoms of postoperative delirium include visual hallucinations, auditory hallucinations, disorientation, aggression and poriomania.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative delirium occurs at an incidence rate of 15-35% following gastrointestinal (GI) surgery in the elderly [1][2][3] . Symptoms of postoperative delirium include visual hallucinations, auditory hallucinations, disorientation, aggression and poriomania.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The incidence is approximately 87% in old patients requiring intensive care. Linda et al [14] found that in 35% postoperative colorectal operative patients aged ≥50 years, at least one episode of delirium was observed within the first 3 days after surgery; it was observed within the first 24 h in 21% patients and on the second (9%) and third (7%) day in some patients. In the present study, the incidence of POD was 9.09% in the Group A patients and 7.2% in the Group B patients, which is contrary to findings in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…[15] This test is not specific to POD, but it could give significant results when applied on the third day after surgery. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In young patients, cognitive deficits were observed in tests applied on the second day after surgery. [17] It was argued that postoperative mental state tests should be applied 1 week after major surgery at the earliest to eliminate anesthetic substances and metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Although varying incidence rates have been reported, it has been stated to occur in 37% of hospitalised patients [25][26][27]. In a study by Sharma et al [28] of elderly patients (mean age, 77 ± 1 years) who underwent surgery for a hip fracture under general anaesthesia, recovery room delirium was determined at a prevalence of 45% and the extent of the high risk group (ASA III) with preoperative dementia was reported to be related to postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%